Organized violence : capitalist warfare in Latin America - Paley, Dawn, 1981-; Granovsky-Larsen, Simon (University of Regina Press, 2019)
"Official stories from media centers in New York and Mexico City say that most violence in Latin America is a product of the drug trade. Organized Violence exposes how that narrative serves corporate and state interests and de-politicizes situations that have more to do with coal, oil, or rare wood extraction than with cocaine. Global capital and violence reinforce conditions that fortify the current economic order, and whether it be the military, police, or death squads that pull the trigger, economic expansion benefits from the violent elimination of the opposition, who are most often dispossessed Indigenous people."--